2007
DOI: 10.1093/pcp/pcl045
|View full text |Cite
|
Sign up to set email alerts
|

Protophloem Differentiation in Early Arabidopsis thaliana Development

Abstract: During Arabidopsis embryogenesis, procambial cells undergo coordinated, asymmetric cell divisions, giving rise to vascular precursor cells (protophloem and protoxylem precursors). After germination, these cells terminally differentiate into specialized conducting cells, referred to as protophloem and protoxylem cells. Few readily identifiable markers of the onset of specification and differentiation are available, hampering the molecular genetic analysis of protophloem development. Confocal microscopy was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
95
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(101 citation statements)
references
References 32 publications
6
95
0
Order By: Relevance
“…No expression was detected in developing embryos or in seeds before germination. Therefore, NaKR1 is not expressed in the earliest protophloem cells that differentiate in mature embryos (Bauby et al, 2007). By 2 DAG, NaKR1 expression was observed in vascular tissue throughout the seedlings.…”
Section: Nakr1 Expression and Root Phenotypesmentioning
confidence: 91%
“…No expression was detected in developing embryos or in seeds before germination. Therefore, NaKR1 is not expressed in the earliest protophloem cells that differentiate in mature embryos (Bauby et al, 2007). By 2 DAG, NaKR1 expression was observed in vascular tissue throughout the seedlings.…”
Section: Nakr1 Expression and Root Phenotypesmentioning
confidence: 91%
“…Indeed, analysis of pBRX::GUS expression in embryos revealed that BRX is ubiquitously expressed at early stages and becomes restricted to the (incipient) vasculature in the mature embryo and at later stages of (adult) development (Fig. 1H-K) (Bauby et al, 2007).…”
Section: Research Articlementioning
confidence: 98%
“…Higher resolution imaging of aniline blue-stained plates using a UV laser on a single-photon confocal microscope leads to rapid aniline blue bleaching, but imaging could be possible with lower energy multiphoton microscopy (A. Schulz, personal communication), deconvolution methods, and the pore number calculation introduced in Figure 6. The Bauby et al, 2007), as well as the cell division zone of the expanding root tip (Beemster and Baskin, 1998), demonstrate an mCitrine signal. Bar 5 100 mm.…”
Section: Analysis Of Se Geometry and Estimates Of Fluid Mechanical Comentioning
confidence: 99%
“…Transmission electron microscopy is a potential alternative (Kü hn et al, 1997;Ehlers et al, 2000;Turgeon et al, 2001) but lacks the three-dimensional perspective needed for good quantitative measurements, it requires more time to implement than light microscopy, and it is inappropriate for statistical sampling of large amounts of tissue. Likewise, exogenously applied fluorochromes (Oparka et al, 1995;Knoblauch and van Bel, 1998;Knoblauch et al, 2001;Martens et al, 2006;Bauby et al, 2007) and sieve element (SE)-specific antibodies, like RS6 (Khan et al, 2007), have proven their utility, but none of the fluorochromes is specific to the phloem and the use of antibodies is expensive and time consuming, lessening the opportunity for fast and direct observation of phloem cells alone.…”
mentioning
confidence: 99%
See 1 more Smart Citation